Oligodendroglial primary cilium heterogeneity during development and demyelination/remyelination - Delfino, Giada; Bénardais, Karelle; Graff, Julien; Samama, Brigitte; Antal, Maria Cristina; Ghandour, M. Said; Boehm, Nelly (Frontiers in Cellular Neuroscience, 2022)
The primary cilium (PC) has emerged as an indispensable cellular antenna essential for signal transduction of important cell signalling pathways. The rapid acquisition of knowledge about PC biology has raised attention to PC as a therapeutic target in some neurological and psychiatric diseases. However, the role of PC in oligodendrocytes and its participation in myelination/remyelination remain poorly understood. Oligodendrocyte precursor cells (OPCs) give rise to oligodendrocytes during central nervous system (CNS) development. In adult, a small percentage of OPCs remains as undifferentiated cells located sparsely in the different regions of the CNS. These cells can regenerate oligodendrocytes and participate to certain extent in remyelination. This study aims characterize PC in oligodendrocyte lineage cells during post-natal development and in a mouse model of demyelination/remyelination. We show heterogeneity in the frequency of cilium presence on OPCs, depending on culture conditions in vitro and cerebral regions in vivo during development and demyelination/remyelination. In vitro, Lithium chloride (LiCl), Forskolin and Chloral Hydrate differentially affect cilium, depending on culture environment and PC length correlates with the cell differentiation state. Beside the role of PC as a keeper of cell proliferation, our results suggest its involvement in myelination/remyelination.